2012
DOI: 10.3354/meps09444
|View full text |Cite
|
Sign up to set email alerts
|

Multi-element otolith fingerprints unravel sea−lagoon lifetime migrations of gilthead sea bream Sparus aurata

Abstract: Precise knowledge of lifetime migrations is vital in exploited fish species, since all essential habitats must be protected to maintain sustainable stock levels. The present study used multi-element otolith fingerprints of the gilthead sea bream Sparus aurata (L.) to discriminate its main juvenile and adult habitats in the Languedoc-Roussillon region (Gulf of Lions, northwest Mediterranean) and infer the lifetime migrations of 12 individuals from the area (11 from the present day and 1 from the Roman era). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 81 publications
5
65
0
Order By: Relevance
“…The facultative behavior of S. aurata in using coastal lagoons as nursery habitats for larvae, as observed in the Mediterranean Sea (Mercier et al, 2012;Tournois et al, 2013), confirms previous observations made in the Ria Formosa lagoon. The larvae of Sparidae were among the most abundant in this lagoon, and most of these larvae were post-flexion larvae collected during flood tides (Chícharo and Teodósio, 1991).…”
Section: Response Of Sparus Aurata Larvae To Odor Cuessupporting
confidence: 78%
See 2 more Smart Citations
“…The facultative behavior of S. aurata in using coastal lagoons as nursery habitats for larvae, as observed in the Mediterranean Sea (Mercier et al, 2012;Tournois et al, 2013), confirms previous observations made in the Ria Formosa lagoon. The larvae of Sparidae were among the most abundant in this lagoon, and most of these larvae were post-flexion larvae collected during flood tides (Chícharo and Teodósio, 1991).…”
Section: Response Of Sparus Aurata Larvae To Odor Cuessupporting
confidence: 78%
“…aurata may ingress into coastal lagoons as larvae (as early as pre-metamorphic larvae) or as juveniles during spring (Mercier et al, 2012;Tournois et al, 2013), returning to the coast during autumn (Mercier et al, 2012). Adults might reingress into coastal lagoons several times during their life even if they spent the juvenile phase at sea (Mercier et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After hatching at sea from De cember to February, a large proportion of the juveniles colonise coastal lagoons in March and April for foraging (Mercier et al 2011, Isnard et al 2015 before returning to the open sea in October and November to overwinter, when lagoon water temperatures drop (Audouin 1962, Lasserre 1974, Mercier et al 2012). In the Gulf of Lions, 2 lagoons, located about 30 km apart and offering very different nursery habitats, have been studied: (1) the Mauguio (MA) lagoon (also known as Etang de l'Or), which is shallow and highly productive, with warm summer temperatures and wide sali nity variations; and (2) the Thau (TH) lagoon, which is larger and deeper and ecologically more similar to the coastal marine environment due to major connections with the Mediterranean (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the Gulf of Lions, 2 lagoons, located about 30 km apart and offering very different nursery habitats, have been studied: (1) the Mauguio (MA) lagoon (also known as Etang de l'Or), which is shallow and highly productive, with warm summer temperatures and wide sali nity variations; and (2) the Thau (TH) lagoon, which is larger and deeper and ecologically more similar to the coastal marine environment due to major connections with the Mediterranean (e.g. Mercier et al 2012, Tournois et al 2013 and references therein). Using candidate gene markers located in the proximal promoter of the growth hormone (GH) and prolactin (Prl) genes, Chaoui et al (2012) found non-neutral allele frequency shifts between young juveniles caught in marine and lagoon habitats and interpreted these patterns as a footprint of post-settlement selection.…”
Section: Introductionmentioning
confidence: 99%